2010
DOI: 10.3386/w16089
|View full text |Cite
|
Sign up to set email alerts
|

Is it Live or is it Internet? Experimental Estimates of the Effects of Online Instruction on Student Learning

Abstract: We appreciate the financial support of the National Science Foundation and the U.S. Department of Education (via the National Center for the Analysis of Longitudinal Data in Education Research.) We are grateful to the introductory microeconomics professor and the large university that permitted us to randomly assign students to live and online versions of the same class. All errors are our own, and our results and conclusions do not necessarily reflect the views of the National Science Foundation, U.S. Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
167
6
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(183 citation statements)
references
References 6 publications
7
167
6
3
Order By: Relevance
“…Thus, while we compare the results of the same student across blended learning and traditional lecturing, Joyce et al (2014) compare students across the control and treatment groups. Similarly to Figlio et al (2013), they show that there was a small difference in performance favouring the traditional teaching treatment.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Thus, while we compare the results of the same student across blended learning and traditional lecturing, Joyce et al (2014) compare students across the control and treatment groups. Similarly to Figlio et al (2013), they show that there was a small difference in performance favouring the traditional teaching treatment.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, there is a potential selfselection bias in that only students and instructors who would prefer an online format might have volunteered for it. Figlio et al (2013) reported on an experiment where controls were significantly more robust than those in the literature reviewed above. In particular, they reported on an experiment conducted in a large (1,600-2,600 students per semester) principles of microeconomics class taught by a single instructor at a large researchintensive university.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the performance of the students is negatively affected if the hybrid classes are based in large lecture halls. Figlio, Rush, and Yin (2010) show that the face-to-face learning outperforms eLearning for low-achievers, males, and Hispanic students. Xu and Jaggars (2013)show the ineffectiveness of eLearning for community college students.…”
Section: Current Research In Elearningmentioning
confidence: 96%
“…A spate of other analyses followed. As no surprise, some meta-analyses have found that online learning is no different or superior (Bernard et al 2004;Zhao et al 2005;Caldwell 2006;Means et al 2009), while others have found the opposite (Rovai 2002;Figlio et al 2010;Tanyel and Griffin 2014). In particular, it has been found that online math courses -especially at the community college level -suffer from low retention rates (Mensch 2010;Xu and Jaggars 2011).…”
Section: Fostering Ql In a Problem-based Online Learning Environmentmentioning
confidence: 99%